Peculiar clinical presentation of COVID-19 and predictors of mortality in the elderly: A multicentre retrospective cohort study. (April 2021) - Bavaro, D.F.; Diella, L.; Fabrizio, C.; Sulpasso, R.; Bottalico, I.F.; Calamo, A.; Santoro, C.R.; Brindicci, G.; Bruno, G.; Mastroianni, A.; Buccoliero, G.B.; Carbonara, S.; et al.
Highlights: Frail elderly COVID-19 patients showed frequent extrapulmonary signs and symptoms. Frailty, dehydration and mechanical ventilation predicted mortality in the elderly. Secondary infections and metabolic complications should be considered in the elderly. Abstract: Background: The spectrum of COVID-19 clinical manifestations is not yet known. In the elderly, mortality and extrapulmonary involvement appears more frequent than expected. Methods: A multicentre-retrospective-case-series study of COVID-19 patients, aged ≥65 years, hospitalised between March 1 and June 15, 2020. Patients were classified at admission into 3 groups based on their Clinical Frailty Scale (CFS) score: 1–3 (group A), 4–6 (group B) and 7–9 (group C). Results: Of the 206 patients in the study, 60 (29%) were assigned to group A, 60 (29%) to B and 86 (42%) to C. Significantly more frequent in group C than in B or A were: mental confusion (respectively 65%, 33%, 7%; P  < 0.001), kidney failure (39%, 22%, 20%; P  = 0.019), dehydration syndrome (55%, 27%, 13%; P  < 0.001), electrolyte imbalance (54%, 32%, 25%; P  = 0.001), and diabetic decompensation (22%, 12%, 7%; P  = 0.026). Crude mortality was 27%. By multivariate logistic regression model independent predictors of death were male sex (adjusted odds ratio (aOR) = 2.87, 95%CI = 1.15–7.18), CFS 7–9 (aOR = 9.97, 95%CI = 1.82–52.99), dehydration at admission (aOR = 4.27, 95%CI = 1.72–10.57) and non-invasive/invasive ventilation (aOR = 4.88, 95%CI = 1.94–12.26). Conclusions: Elderly patients with a high CFS showed frequent extrapulmonary signs at admission, even in the absence of lung involvement. These findings, along with a high CFS, predicted a significant risk of mortality.